Spouse Support, Innovative Behaviour and Entrepreneurial Effectiveness of Women-Owned Agricultural Small and Medium Enterprises (SMEs) in Uganda (International Journal of Applied Research in Management and Economics, 2024)
The purpose of this study is to establish whether innovative behaviour mediates the relationship between spouse support and entrepreneurial effectiveness of Women-owned agricultural Small and Medium Enterprises in Uganda. This is a cross-sectional and correlational study. A self-administered questionnaire was utilised to collect information from women-owned agricultural SMEs in Uganda's central region. In order to determine the mediating role of innovative behaviour, the Statistical Package for the Social Sciences (SPSS.25) and Medgraph - Excel Version were used to conduct correlation, hierarchical regression and mediation analyses on the data. Study findings revealed that spouse support and innovative behaviour positively and significantly explicate the entrepreneurial effectiveness of Women-owned agricultural SMEs. In addition, spouse support is positively and significantly associated with innovative behaviour and finally, innovative behaviour partially mediates the association between spouse support and entrepreneurial effectiveness. The study established that innovative behaviour partially mediates spouse support and entrepreneurial effectiveness of women-owned agricultural SMEs, unlike extant studies that interrogated the direct relationship between the study variables in predicting entrepreneurial effectiveness.